2016
DOI: 10.1513/annalsats.201604-246oc
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide-Resistant Mycobacterium avium Complex Lung Disease: Analysis of 102 Consecutive Cases

Abstract: Inappropriate prescription patterns and deviations from the standard treatment because of adverse drug reactions appeared to be the main causes of macrolide resistance in this patient series. Drug sensitivity testing should be performed at diagnosis to identify macrolide resistance and patients who may benefit from other therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 30 publications
5
90
1
1
Order By: Relevance
“…Macrolides are the cornerstone drugs in the treatment of NTM-LD (4)(5)(6). Therefore, patients with macrolide-resistant MAC-LD (22)(23)(24)(25) or macrolide-resistant MABC-LD, including patients with lung disease caused by both isolates with intrinsic resistance and isolates with acquired resistance (26)(27)(28)(29)(30), have a very poor prognosis. In our study, salvage therapy with AMK inhalation was added to the existing (failing) regimens in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…Macrolides are the cornerstone drugs in the treatment of NTM-LD (4)(5)(6). Therefore, patients with macrolide-resistant MAC-LD (22)(23)(24)(25) or macrolide-resistant MABC-LD, including patients with lung disease caused by both isolates with intrinsic resistance and isolates with acquired resistance (26)(27)(28)(29)(30), have a very poor prognosis. In our study, salvage therapy with AMK inhalation was added to the existing (failing) regimens in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…The NTM species of the Mycobacterium avium complex (MAC ), M. kansasii and M. abscessus have been implicated in pulmonary human disease (McShane & Glassroth, ), with MAC being a principal culprit of clinically diagnosed pulmonary NTM infections (Mirsaeidi, Farshidpour, Ebrahimi, Aliberti, & Falkinham, ; Prevots & Marras, ; Schluger, ). Despite M. avium pathogenesis not being entirely delineated in humans, it is arguably one of the most characterized and studied NTM (Appelberg, ; Appelberg et al, ; Bermudez et al, ; Field, Fisher, & Cowie, ; Johnson & Odell, ; Morimoto et al, ; Stout et al, ). Typical contraction of M. avium stems from the inhalation or ingestion of aerosolized mycobacteria or mycobacterial droplets (Appelberg, ; Appelberg et al, ; Bermudez et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, bacteriostatic activity has been demonstrated against M. tuberculosis strains and slow grower mycobacteria ( M. avium ) showing growth after clearance of the compounds. The activity at very low doses of selected compounds ( PS4 , PS9 , PS14 , and PS18 ) on M. avium could be of potential interest as this mycobacterium infects immunodepressed patients and resistance to macrolides is increasing . Moderate bacteriostatic activity has been previously shown for usnic acid, and some derivatives .…”
Section: Discussionmentioning
confidence: 99%